JURIDICAL ANALYSIS OF DEFAULT RESOLUTION IN COOPERATION CONTRACT FOR FIBER OPTIC CABLE ACQUIREMENT (DROP CABLE) - Wijayani, Putu Megabalinda Pradnya; Wesna, Dr. Putu Ayu Sriasih; Utama, Dr. I Wayan Kartika Jaya (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2024)
A contract is an agreement between two or more people, where they promise each other to do something. An agreement is made by two parties who need each other and agree to comply with respective obligations. Default occurs when one of the parties does not implement or is negligent in fulfilling the obligations agreed upon in the agreement. This research is concerned about the forms of cooperation contract for fiber optic cable acquisition (drop cable) between PT Fibeart Trans Network and PT Jagat Karya Putra Indonesia, and its legal consequences based on Court Decision Number 195/PDT.G/2023/PN JKT.SEL. This research uses normative legal research methods, to provide a legal basis in determining whether a certain situation is true or false and the consequences of default under the law. This fiber optic cable cooperative contract was legally made by parties who have legal capacity, with a halal causa, and was written in a writing affixed with a statement letter by a notary on December 11, 2021. Based on Court Decision Number 195/Pdt.G/2023/PN JKT.SEL, both parties have agreed to purchase and sell fiber optic cables, but PT Jagat Karya Putra Indonesia did not fulfill its obligation to pay the remaining payments to PT Fibeart Trans Network, which caused them to default.